Pozorne dobro, ukryte zło: edukacja komercyjna w mediach - Marek Lis (Jesuit University Ignatianum in Krakow, 2017)
Among the four models of communication described by D. McQuail (transmission model; ritual or expressive model; publicity model; reception model), the publicity model reveals specialimportanceforthemassmedia,sinceit depicts communication through the media as gaining audience, treated as the goal of advertising and consumers. The dangers resulting from the commercial usage of the audience are noticed, among others, in the Catholic Church documents, as well as by researchersexaminingtheconsumersociety.Theauthordoesnot negate the importance of advertising in contemporary world. However, he suggests a critical examination of the functions performed by the media. Apart from information, correlation, continuation, entertainment and mobilization, the commercial function is becoming more and more significant, with the media beingmeretoolsofadvertising; the function which prepares the audience for the role of consumers.